Performance evaluation of ODMAC protocol for WSNs powered by ambient energy. (8th February 2022) - Hmidi, Zohra; Kahloul, Laid; Benharzallah, Saber; Hamani, Nadia
Designing a good MAC protocol remains a challenge. Such a protocol has to guarantee access to the medium while reducing energy consumption. With the appearance of energy harvesting-wireless sensor networks (EH-WSNs), energy is no longer a problem but the challenge now is that each sensor remains in its energetically sustainable state as much as possible. This paper proposes a formal study of on demand MAC (ODMAC) one of the well-known protocols proposed for EH-WSNs. An analysis through statistical model checking is made where properties that guarantee the protocol's correctness are verified and a performance evaluation of important aspects is achieved.